THE ROLE OF PEERS IN SUPPORTING THE LEARNING OF STUDENTS WITH VISION DISABILITIES IN INCLUSIVE CLASSROOMS IN HIGHER EDUCATION - Hyacintha Rafasyandana Athaya; Mahardika Supratiwi (Journal of Disability, 2025)
Blind students in inclusive college classes face various challenges, especially in accessing visual materials and actively participating in the learning process. Based on these problems, this study aims to examine the role of peers in supporting the learning of students with visual impairments in higher education environments. This study uses a qualitative, phenomenological approach to explore the subjective experiences of non-disabled students who accompany blind students. The subject of the study was a student of the Special Education Study Program who actively helped his blind friend in academic and social activities in an inclusive class. Data were collected through in-depth interviews and observations, then analyzed using the Miles and Huberman interactive analysis model. The results showed that peers provided support that included academic aspects (such as explaining visual materials and providing digital notes), emotional (increasing self-confidence), social (being a discussion partner), and technical (campus navigation). The conclusion of this study shows that the role of peers contributes significantly to creating an inclusive learning environment, supporting academic success, and strengthening social relations of blind students in higher education.